Novel Bodipy- triazine conjugates: Synthesis and the generation of singlet oxygen. (August 2017) - Eçik, Esra Tanrıverdi; Şenkuytu, Elif; Çoşut, Bünyemin
Abstract: Novel Bodipy decorated triazine conjugates were successfully designed and synthesized by the click reaction of azido functionalized di-styryl Bodipys with propargyl alkoxide substituted triazine. The identities of newly synthesized compounds were confirmed by using 1 H and 13 C NMR spectroscopies. The molecular structure of propargyl alkoxide substituted triazine was also determined by X-ray crystallography. The photophysical (fluorescence lifetime and fluorescence quantum yield) and photochemical (the singlet oxygen generation capabilities and appropriate photo degradation by light irradiation) properties of Bodipy- triazine conjugates were investigated for determination of their fluorescence and photosensitizer abilities. These results will provide further insight and motivation for development of Bodipy based singlet oxygen photosensitizer systems. Graphical abstract: Novel Bodipy decorated triazine conjugates have been successfully synthesized. The photophysical and photochemical properties of these conjugates have investigated for determination of their fluorescence and photosensitizer abilities. Bodipy-triazine conjugates are proposed as potential singlet oxygen photosensitizers. Highlights: Novel Bodipy-Triazine conjugates were synthesized. The new conjugates showed high singlet oxygen quantum yields. Bodipy-Triazine conjugates were proposed as potential photosensitizers.